823 CD4 T cells are essential for an anti-tumor effect in a B78 murine melanoma tumor model. (9th November 2020) - Feils, Arika; Heck, Mackenzie; Hoefges, Anna; Carlson, Peter; Zangl, Luke; Patel, Ravi; Kravtsov, Dmitriy; Hank, Jacquelyn; Morris, Zachary; Rakhmilevich, Alexander; Sondel, Paul; Erbe, Amy
Abstract : Background: Mice bearing B78 melanoma tumors can be cured using an in situ vaccine (ISV) regimen that includes radiation (RT) together with immunocytokine (tumor-targeting mAb conjugated to IL-2). B78 melanoma cells, derived from B16 cells, express minimal to no MHC-I but express MHC-II upon IFN-g/TNF-a stimulation. Although B78 cells are primarily MHC-I-deficient, an increased CD8 T cell infiltration into the tumor microenvironment (TME) has been shown following ISV. 1 To further investigate the potential role of specific immune cell lineages in the B78 anti-tumor response to ISV, immune subset depletion studies and flow cytometric analyses were performed. Methods: C57BL/6 mice bearing B78 tumors were depleted of immune cell subsets with mAbs (anti-CD4, anti-CD8, anti-NK1.1, or Rat IgG control) for 3 weeks during the course of treatment. Treatment groups included no treatment, RT (12 Gy), or ISV (RT D0 and immunocytokine D5-D9). 6 mice/group (repeated three times) were followed for survival/tumor growth, and flow cytometry studies included 4 mice/group, sacrificed on D8 and D13 following the start of ISV. Results: Mice depleted of CD4 T cells during the course of ISV showed a significant reduction of anti-tumor effect as compared to mice treated with ISV/Rat IgG (p Conclusions: These studies suggest that CD4 T cells are essential for an anti-tumor response in the B78 melanoma model. In vivo depletion data show that CD4 T cells, but not CD8 or NK cells, are required for a decrease in tumor growth via ISV. Flow cytometric analyses suggest an interplay between CD4 and CD8 T cells as indicated by a decrease in CD8/IFN-g expression following ISV in the absence of CD4 T cells. The role that MHC-I and MHC-II expression plays in this CD4/CD8 T cell anti-tumor response is under investigation. In future studies, B78 melanoma may serve as a critical syngeneic model for development of more effective immunotherapy treatment regimens. Ethics Approval: All animal experiments were performed in accordance with protocols approved by Animal Care and Use Committees of the University of Wisconsin-Madison. Reference: Morris Z, Guy E, Francis D, et al. In situ tumor vaccination by combining local radiation and tumor-specific antibody or immunocytokine treatments. Cancer Res 2016;76(13):3929-3941.